End-of-life care in cancer and dementia: a nationwide population-based study of palliative care policy changes. Issue Volume 12:Issue e3(2022) (17th September 2019) - Kuo, Lou-Ching; Lee, Jung Jae; Cheung, Denise Shuk Ting; Chen, Ping-Jen; Lin, Chia-Chin
Abstract : Objectives: The National Health Insurance programme started providing coverage for inpatient care in palliative care (PC) units of acute care hospitals in 2000; however, initially, only PC provided to patients with terminal cancer was covered. A PC policy that enabled PC reimbursement for patients with dementia was implemented in 2009. However, the association of this PC policy with end-of-life care remains unclear. The study aims to compare the association of the PC policy with end-of-life care between patients with dementia and patients with cancer during the last 6 months of their lives. Methods: We analysed the claims data of 7396 patients dying with dementia (PDD) and 24 319 patients dying with cancer (PDC) during 1997–2013. Results: Among PDC, while the percentage of receiving PC increased from 3.6% in 1999 to 14.2% by the end of 2000 (adjusted OR (aOR)=4.07, 95% CI 2.70 to 6.13) and from 20.9% in 2010 to 41.0% in 2013 (aOR=1.40, 95% CI 1.33 to 1.47), vasopressor use decreased from 71.6% in 1999 to 35.5% in 2001 (aOR=0.90, 95% CI 0.82 to 0.98). Among PDD, PC use increased from 0.2% in 2009 to 4.9% in 2013 (aOR=2.05, 95% CI 1.60 to 2.63) and cardiopulmonary resuscitation use decreased from 17.6% in 2009 to 10.0% in 2013 (aOR=0.83, 95% CI 0.76 to 0.90). Conclusions: Implementation of the PC policy in Taiwan was associated with improved PC utilisation among patients with cancer and dementia, which may reduce unnecessary medical care procedures.